2000 tips for lecturers. - Race, Phil (London : Kogan Page, 1999)
Brings together a range of expert tips and guidance for all those lecturing and teaching in higher education. With ideas on all aspects of HE teaching, it covers a range of issues that can crop up in daily working life, and is both a lifeline to new teachers and a handy sourcebook and refresher for more experienced educators.
1. Towards student-centered learning -- 2. Lectures -- 3. Small-group teaching and learning -- 4. Designing and using learning resources -- 5. Assessment -- 6. Feedback, evaluation and external scrutiny -- 7. Looking after yourself -- 8. Getting published.
Includes index.
Keywords: COLLEGE TEACHING; LECTURE METHOD IN TEACHING; LECTURES AND LECTURING; LECTURES; COLLEGE TEACHING -- VOCATIONAL GUIDANCE; LECTURES AND LECTURING -- VOCATIONAL GUIDANCE